2007
DOI: 10.1177/089686080702700517
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Outcomes of Peritonitis after Flexible Colonoscopy in CAPD Patients

Abstract: Objective The ISPD 2005 guidelines for peritonitis recommend antibiotic prophylaxis for patients undergoing colonoscopy with polypectomy while on continuous ambulatory peritoneal dialysis (CAPD) but there is little literature to support this recommendation. This study aimed to look into the risks and outcomes of peritonitis after colonoscopy in CAPD patients. Patients and Methods All records of flexible colonoscopy performed on our CAPD patients from January 1994 to January 2006 were retrieved. Demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
5
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 17 publications
4
62
5
5
Order By: Relevance
“…Because ofloxacin is a racemic mixture consisting of 50% levofloxacin and 50% dextro-ofloxacin (which is biologically inactive), the dose of levofloxacin used in the present study (half the dose of oral ofloxacin used in previous studies) was expected to suffice. We use a similar dose of oral levofloxacin for peritonitis prophylaxis during colonoscopy, with good results (8). Our data support the effectiveness and convenience of this antibiotic regimen for prophylaxis.…”
Section: Discussionsupporting
confidence: 61%
“…Because ofloxacin is a racemic mixture consisting of 50% levofloxacin and 50% dextro-ofloxacin (which is biologically inactive), the dose of levofloxacin used in the present study (half the dose of oral ofloxacin used in previous studies) was expected to suffice. We use a similar dose of oral levofloxacin for peritonitis prophylaxis during colonoscopy, with good results (8). Our data support the effectiveness and convenience of this antibiotic regimen for prophylaxis.…”
Section: Discussionsupporting
confidence: 61%
“…The authors however, indicated that it lacks statistical significance compared with prior antibiotic prophylaxis [33]. Colon biopsy or polypectomy did not appear to further increase the risk of peritonitis in our cohort [34]. Interestingly, the International Society for Peritoneal Dialysis recommended antibiotic prophylaxis before any procedure involving the abdomen or pelvis, including colonoscopy [14].…”
Section: Discussionmentioning
confidence: 66%
“…Bowel hygiene with attention to prevention of constipation is also a good approach. Procedures such as colonoscopy can lead to peritonitis, and therefore the abdomen should be empty of dialysis fluid during these procedures 9. I recommend prophylactic antibiotics prior to the procedure to prevent this complication.…”
Section: Prevention Of Enteric Peritonitismentioning
confidence: 99%
“…I recommend prophylactic antibiotics prior to the procedure to prevent this complication. Such an approach decreases the risk of peritonitis from about 5% to close to 0% 9…”
Section: Prevention Of Enteric Peritonitismentioning
confidence: 99%